Effect of Lanthanum Cerium Cysteine on Cure Characteristics, Mechanical Properties, and Thermooxidative Aging for Natural Rubber. (3rd December 2021) - Zhang, Wentao; Liu, Zhaogang; Li, Shuai; Hao, Wei; Hu, Yanhong; Wu, Jinxiu
Abstract : In this work, a novel additive lanthanum cerium cysteine (LC-Cys), with the molecular formula La0.35 Ce0.65 (Cys)3 Cl3 ·3H2 O, was successfully synthesized through complex decomposition reaction of L-Cysteine and chlorinated rare earths. The effects of additive LC-Cys on cure characteristics, mechanical properties, and thermooxidative aging were investigated. LC-Cys as a multifunctional additive was applied to increase the curing rate and reduce the content of zinc oxide in the presence of the sulfur vulcanization system. It was found that the vulcanizates filled with (5ZnO/2LC-Cys) exhibited the highest modulus, which indirectly indicated the high crosslink and stiffness of the vulcanizates. Moreover, the vulcanizates with LC-Cys showed excellent mechanical properties and resistance to thermooxidative aging. Compared to NR composites filled with normal ZnO, LC-Cys even enhanced the mechanical strength and thermooxidative aging properties with 40% lower ZnO addition.